Evaluation of learning and memory effect of atorvastatin and simvastatin in alprazolam induced amnesia in mice - G., Shashikala; C. H., Jyothi; G. H., Shashikala (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The study was undertaken to evaluate the learning and memory effect of lipid lowering drugs atorvastatin and simvastatin in alprazolam induced amnesic mice. Methods: The study was carried out on albino mice, divided into 4 groups of 6 animals each (either sex, 3-4 months of age, weight 25-30g). Amnesia was induced by administering Alprazolam (2mg/kg for 14 days) in all 4 groups from 1st to 14th day. In addition, group 2, 3 and 4 received Piracetam (400mg/kg), Atorvastatin (5mg/kg) and Simvastatin (5mg/kg) from 8th to 14th day respectively. The learning and memory of the animals was assessed by employing Elevated plus maze (EPM) and Step-down type passive avoidance (SDA) model. Results: Results were compared among the different groups using one way-ANOVA followed by post hoc Tukey’s test. The measured parameters were compared with standard drug Piracetam. In EPM model Atorvastatin (p<0.049) and Simvastatin (p<0.007) were comparable with standard drug Piracetam, whereas in SDA model only simvastatin group (p<0.001) showed significant result. Conclusions: In EPM model, both the statins showed significant improvement in learning and memory in alprazolam induced amnesic mice. However further studies are required to support these observations.